Nano-mechanical and nano-tribological characterisation of self-lubricating MoS2 nano-structured coating for space applications. (February 2023) - Mukhtar, Sheikh Haris; Wani, M.F.; Sehgal, Rakesh; Sharma, M.D.
Abstract: Tribological components cost only a fraction of the entire spacecraft, but they often lead to failures that partially or completely disrupt the spacecraft, resulting in a mission compromise. Mechanical components used in space applications have to withstand extreme environmental conditions, thus inhibiting the use of a liquid-based lubricant. Therefore, solid-based lubricating materials are employed for space applications. In this work, a PVD process was used to deposit a nano-structured coating of MoS2 on AMS 5898 stainless steel. The structure, morphology, and chemical composition were evaluated using X-Ray diffraction, FESEM, EDS, and Raman spectroscopy. The nano-tribological and nano-mechanical behaviour of the developed coating was investigated under various loads. Further, a ramp load nano-scratch test was also used to determine the adherence of the coating to the substrate. Results indicate that the MoS2 nano-structured coating has a polycrystalline structure with basal planes oriented perpendicular to the surface of the substrate. A substantial decrease in coefficient of friction was observed with an increase in applied load, while the wear rate showed an increasing trend with the applied load. A very low coefficient of friction of 0.02 and a low wear rate of 4.69 × 10 −6 mm 3 /m were obtained during this study. The hardness and Young's modulus increased with an increase in the indentation load due to the reverse indentation size effect and substrate effect, respectively. The maximum values of hardness and Young's modulus were determined to be 9.46 GPa and 350.50 GPa, respectively. Furthermore, the coating adhered well to the substrate, with an adhesion strength of 1286.5 µN, and a coefficient of friction of 0.18 was reported during scratch testing. Highlights: Cutting and Polishing of disc samples of AMS 5898 stainless steel. Discs were polished to achieve mirror finishing with surface roughness values less than 10 nm. Coating of MoS2 was applied using PVD magnetron sputter coating machine. The coating thickness was measured to be 76 nm using a 3D profilometer. The thickness of the coating was measured to be 76 nm. The surface roughness of the coating was determined using SPM and was found to be less than 5 nm. Mechanical properties of coating, such as hardness, Young's modulus and scratch adhesion were measured using Nano mechanical system. Tribological tests were conducted using nano-tribometer to measure friction and wear properties of the nano-coating of MoS2 . Techniques such as, optical microscopy, FESEM with EDS, Raman spectroscopy, XRD, etc. were used to identify causes of friction/wear and wear mechanisms.